Muskuloskeletal aldring, arbejdsevne og "sundhedsbrøken" - Møller, Anne; Reventlow, Susanne (Tidsskrift for Forskning i Sygdom og Samfund, 2012)
Physical activity in leisure-time is recommended by authorities as healthy while physical activity at work is often considered to be harmful to your health. In Denmark the term ‘nedslidning’ is used to describe the gradual physical deterioration due to exposures in the work environment. This article presents a review of the literature about physical work and health, and the historical and present use of the term ‘nedslidning’ is described. Instead of using the not vey specific term ‘nedslidning’, the article suggests that the process of deterioration is seen as part of the musculoskeletal ageing process. The reader is presented to a ’life course perspective’ on the aging process and to a ‘life course perspective’ on the relationship between the physical activity in work life and the following physical function in midlife. The paper concludes with a recommendation of the use of these perspectives in future occupational research and in daily life, where professionals are working with the relationship between work environment and health.